Seleucia Pieria in the Classical Period "A study of the information contained in historical texts and archaeological inscriptions" (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
Seleucus I, also known as Seleucus Nikator, after eliminating his opponents and establishing a vast empire, founded many cities, following the policy of his leader, Alexander the Great. When he built the cities, he chose important strategic locations controlling the trade routes crossing Syria and Mesopotamia. Among the many cities he founded, the Tetrapolis (sister cities) that he built in northern Syria are famous: Antioch - Apamea - Laodicea - Seleucia Pieria, which is the subject of this research.This research deals with the geographical location of Seleucia-Pieria and its economic, military and religious importance. It will also talk about the legendary founding of the city and describe it as it was reported by historians of the classical period, and also as it was reported by European travelers who visited it, in addition to describing its port and facilities. The research will examine the city’s political and historical conditions in the Hellenistic, Roman, and Byzantine periods, as well as its religious and economic conditions.This research will attempt to help researchers and specialists study the conditions of Syrian cities in that mysterious and important period of Syrian history in the classical period, which information about is brief and very few in Arabic references.